Association between positive emotions, depression and functional recovery in post-stroke patients / Low Jong Sern - Low, Jong Sern (2018)
Background and Objective: Stroke is a major health problem in Malaysia which leads to substantial disease burden to the country. Post-stroke depression was well studied in association with functional outcome. However, there was no study on positive emotion in post-stroke patients in local setting. The objective of this study is to assess positive emotion and depression in post-stroke patients in Hospital Pulau Pinang and their association with functional recovery. Method: A total of 136 patients at 6-12 weeks post stroke, were recruited from Occupational Therapy Unit and Rehabilitation Clinic Hospital P. Pinang. All the patients were given Demographic and Clinical Data Questionnaire, Positive Emotion Rating Scale (PERS) or Malay version Positive Emotion Rating Scale (PERS-M) and Montgomery-Asberg Depression Scale-Self (MADRS-S) or Malay version Montgomery-Asberg Depression Scale-Self (MADRS-BM). Patients were also assessed for functional status using Modified Barthel Index (MBI) Results: 65.4% of patients have shown to have good positive emotion and 23.5% of patients have depression. Patients with the length of stay less than 5 days were 7.3 times more likely to have good positive emotion and 12.3 times less likely to have depression. Patients with less than 3 medical co-morbidities were 4.3 times less likely to have depression. Based on bivariate analysis, both total PERS and total MADRS-S scores were significantly associated with functional independence and functional recovery in 6 to 12 weeks post-stroke. However, using multiple linear regression, only total PERS, but not total MADRS-S, was significantly associated with both functional independence and functional recovery. Other factors that showed significant in iv functional independence were the length of stay and MBI (discharge). Whereas in functional recovery, significant factors were spouse and age. Conclusion: Length of stay of less than 5 days was 12.3 times less likely to have depression and 7.3 times more likely to have good positive emotion. Positive emotion is a stronger predictor of functional independence and function recovery compared to post-stroke depression. Other strong predictors of functional outcome were the length of stay, MBI(discharge), patient with spouse and age.